2023
DOI: 10.1371/journal.pbio.3002010
|View full text |Cite
|
Sign up to set email alerts
|

Local and global reward learning in the lateral frontal cortex show differential development during human adolescence

Abstract: Reward-guided choice is fundamental for adaptive behaviour and depends on several component processes supported by prefrontal cortex. Here, across three studies, we show that two such component processes, linking reward to specific choices and estimating the global reward state, develop during human adolescence and are linked to the lateral portions of the prefrontal cortex. These processes reflect the assignment of rewards contingently to local choices, or noncontingently, to choices that make up the global r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 101 publications
(274 reference statements)
1
0
0
Order By: Relevance
“…We also found that previous reward enhanced the effects of current reward and effort on decision making. This results aligns with prior evidence that it may provide context for the current decision, potentially as a direct comparison with the current reward 63 or as a measure of recent reward history that captures the richness of the environment or global reward state 21,65 . Although the rewards on consecutive trials were independent in our laboratory paradigm, PFC likely tracks reward context because rewards have strong temporal correlations in real world environments.…”
Section: Discussionsupporting
confidence: 86%
“…We also found that previous reward enhanced the effects of current reward and effort on decision making. This results aligns with prior evidence that it may provide context for the current decision, potentially as a direct comparison with the current reward 63 or as a measure of recent reward history that captures the richness of the environment or global reward state 21,65 . Although the rewards on consecutive trials were independent in our laboratory paradigm, PFC likely tracks reward context because rewards have strong temporal correlations in real world environments.…”
Section: Discussionsupporting
confidence: 86%
“…We also found that previous reward enhanced the effects of current reward and effort on decision making. This result aligns with prior evidence that it may provide context for the current decision, potentially as a direct comparison with the current reward ( 67 ) or as a measure of recent reward history that captures the richness of the environment or global reward state ( 24 , 69 ). Although the rewards on consecutive trials were independent in our laboratory paradigm, PFC likely tracks reward context because rewards have strong temporal correlations in real-world environments.…”
Section: Discussionsupporting
confidence: 84%
“…Compared to adults who predominantly exert effort strategically as an instrument to maximize rewards and minimize effort (Rodman et al, 2021), adolescents seem less sensitive to effort costs, thus, exerting more effort than a task requires (Sullivan-Toole et al, 2019). These differences might be influenced by changes in striving for autonomy (e.g., Steinberg & Morris, 2001) and in the neural (e.g., Wittmann et al, 2023) or hormonal system (e.g., Buchanan et al, 1992;Cyranowski et al, 2000) during adolescence, and on the other hand, rising opportunity costs of effort with aging (Cardini & Freund, 2021).…”
Section: Developmental Aspectsmentioning
confidence: 99%